1985
DOI: 10.1037/h0089642
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for prevention: Role flexibility and affective reactivity as factors in family coping.

Abstract: A model of family adaptation to chronic illness is described. The model predicts that, when family rules allow for expression of emotions and when family roles are flexible, the adaptation process will be effective. When family rules prohibit emotional expression or family roles are inflexible, adaptation will be ineffective. Ineffective adaptation is characterized by a pile-up of stressors that are related to the adaptation process and that increase the likelihood of negative mental health outcomes for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Snidies have consistently shown chat prohibition of emotional expression has adverse effects on a family's adaptation to chronic illness [51,52]. Thompson et nl [23] and Miller ct ill. [24] both found emotion-focused strategies positively associated with poor adjustment.…”
Section: Relationship Between Maternal and Paternal Copingmentioning
confidence: 99%
See 1 more Smart Citation
“…Snidies have consistently shown chat prohibition of emotional expression has adverse effects on a family's adaptation to chronic illness [51,52]. Thompson et nl [23] and Miller ct ill. [24] both found emotion-focused strategies positively associated with poor adjustment.…”
Section: Relationship Between Maternal and Paternal Copingmentioning
confidence: 99%
“…A child with a disability may necessitate many changes in a fainily's lifestyle [52]. If the family does not respond to the need to change, this may become an additional source of stress [65].…”
Section: Copitjg In Relation To Family Environmentmentioning
confidence: 99%
“…Examples include family cohesion (for example, Barbarin, Hughes, & Chesler, 1985;Olson, Sprenkle, & Russell, 1979); sex role behavior (Downey, 1984); marital power (Mirowsky, 1985); family privacy (Pittman & Lloyd, 1988); and adaptability or role flexibility (Koch, 1985). Examples include family cohesion (for example, Barbarin, Hughes, & Chesler, 1985;Olson, Sprenkle, & Russell, 1979); sex role behavior (Downey, 1984); marital power (Mirowsky, 1985); family privacy (Pittman & Lloyd, 1988); and adaptability or role flexibility (Koch, 1985).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Research in family sociology and family health psychology has linked several aspects of family Structure/Organization with the health and functional status of family members. Examples include family cohesion (for example, Barbarin, Hughes, & Chesler, 1985;Olson, Sprenkle, & Russell, 1979); sex role behavior (Downey, 1984); marital power (Mirowsky, 1985); family privacy (Pittman & Lloyd, 1988); and adaptability or role flexibility (Koch, 1985). Also, most family assessment inventories include scales that tap various components of family Structure/Organization, for example, FACES (Olson et al, 1979), Family Environment Scale (Moos & Moos, 1981), and Family Assessment Device (Epstein, Baldwin, & Bishop, 1983), attesting to the importance placed on this domain when considering issues of health and illness.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Family researchers have studied the effects of different styles of expressing and managing emotional experiences on various health‐related problems, although their role in the etiology of disorder is difficult to confirm (Campbell, 1986). Koch (1985) suggested that adaptation to chronic illness is enhanced in families that permit the open expression of emotion. Gottman and Krokoff (1989) showed that, although the overt expression of conflict in couples may be disruptive and problematic, expressiveness is associated with improved levels of marital satisfaction at long‐term followup.…”
mentioning
confidence: 99%